POLA JUMLAH TROMBOSIT PADA ANAK YANG MENDERITA DEMAM DENGUE (DF) DAN DEMAM BERDARAH DENGUE (DHF) DI RSUD Dr H CHASAN BOESOIRIE TERNATE PERIODE JANUARI-NOVEMBER 2019 - Marhaeni Hasan (Fakultas Kedokteran, Universitas Khairun, 2020)
Dengue is an acute virus infectious disease caused by the dengue virus and transmitted by Aedesaegypty mosquitoes with high mortality and morbidity in many regions of the world. Thrombocytopenia is oneof the laboratory parameters in diagnosing dengue virus infection that has the possibility to change day by day.To study the thrombocyte count pattern in dengue fever (DF) and dengue haemorrhagic fever (DHF) inpediatrics patient. This type of research is a cross sectional analytic study with a retrospective design, usingsecondary data from medical records in Pediatrics department of Dr H Chasan Boesoirie distric hospitalduring January-November 2019 period. The research sample was aged <15 years, diagnosis of DF and DHFaccording to WHO 2011 criteria, the data regarding thrombocyte counts, days of sickness, the patient’scharacteristics and for statistical analysis Mann-whitney test was used. On average, the thrombocyte count inDF patients starts dropping by the 4th day. It reaches its lowest point on the 5th day and starts going up on 6thday. In DHF patients, on average, the thrombocyte count drops by the 3rd day, hits lowest point on the 5th, andgoes back up on the 6th day. In DHF patients with shock, the average thrombocyte count on the 3rdday is 50.000cells/mm3 while the lowest count, on average on the 6th day is 42.000 cells/mm3. This number starts going up onthe 7th day. There is a significant difference in the average thrombocyte count between DF and DHF patientson the 3rd, 4th, 5th, and 6th day (p<0.05) . As for DHF patients without shock, a significant difference was foundon the 6th day (51.000 cells/mm3 and 81.000 cells/mm3, p=0.047). There is a significant difference in theaverage thrombocyte counts between DF and DHF patients. The declining count to <100,000 cells/mm3 on the3rd day of sickness has to be taken cautiously in order to prevent from making the shock worse.